Epidemiology of osteoporotic fractures. - Dennison, E; Cooper, C (2000)
Osteoporosis constitutes a major public health problem through its association with age-related fractures. These fractures typically occur at the hip, spine and distal forearm. It has been estimated that the lifetime risk of a hip fracture in white women is 17.5%, with a comparable risk in men of 6%. Hip fractures lead to an overall reduction in survival of about 15% (relative or observed/expected survival at 5 years of 0.83), and the majority of excess deaths occur within the first 6 months following the fracture. Such fractures are also associated with considerable morbidity. Although all vertebral deformities do not come to clinical attention, the lifetime risk of clinically diagnosed vertebral fractures is about 15% in white women. Vertebral fractures tend to be associated with back pain and kyphosis, and also with an impairment of survival, though this is likely to be due to clustering of comorbidity. About one-quarter of clinically diagnosed vertebral deformities result in hospitalization.